The Impact of Lerntagebuch on Learning Outcome of German Writing Skills Through Freizeit Theme - Ellychristina D. Hutubessy; Santiah Santiah; Nastasha Hera Pramesya (STAI Hubbulwathan Duri, 2021)
This study aims to determine the effect of Lerntabeguch on learning outcomes of German writing skills using the freizeit theme. The method used in this study is a quantitative method with a research design of Pretest Posttest Control Group Design. The research was conducted at State Senior High School 31 Jakarta. The research sample was taken by a simple random sampling technique. Data were collected through documents and writing tests. Validity tests were using Pearson Product Moment and reliability using Cronbach Alpha. While the data analysis technique used a t-test. The results showed that the t-count Pretest in the experimental class and control class was 1.108 with t-table at a significance level of = 0.05 and degrees of freedom (DK) = 34. While the results of the t-count Posttest in the experimental class and control class were 3,485. So, there is an effect of using Lerntagebuch on learning outcomes of German writing skills for class XII students related to the topic of Free Time Activities (Freizeit).